ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS USAHA PERTANIAN GAMBIR DI NAGARI TALANG MAUR KECAMATAN MUNGKA KABUPATEN LIMA PULUH KOTA - Laila, Rahmatul; Iryani, Nelvia (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
West Sumatra is one of the provinces that excels in various sectors, one of West Sumatra's superior sectors is the agricultural sector. According to the Coordinating Ministry for Economic Affairs of the Republic of Indonesia, gambier plants are one of the leading commodity contributors which makes West Sumatra superior in the agricultural sector. West Sumatra is able to supply 80-90% of gambier production. The aim of this research is to determine and analyze the influence of farming experience, capital, education and technology on the productivity of gambier farming businesses in Nagari Talang Maur, Mungka District, Lima Puluh Kota Regency. The type of data in this research is primary data obtained from distributing questionnaires and interviews. The method used in this research is the Multiple Linear Regression Test. The research results show that partially farming experience, capital, education and technology have a positive and significant influence on the productivity of gambier agricultural businesses. The results of the research also show that simultaneously all the independent variables in this study have a significant influence on the dependent variable.